Detection of severe acute respiratory syndrome corona virus 2 in cervico-vaginal secretion of COVID-19-affected female: A prospective observational study from India. (June 2021) - Agarwal, Mukta; Basumatary, Swmkwr; Bhusan, Divendu; Pati, Binod Kumar
Background: The novel severe acute respiratory syndrome corona virus 2 (also known as 2019-nCoV) is a highly infectious agent and is declared as a global public health emergency by the World Health Organisation. The main known transmission route of severe acute respiratory syndrome corona virus 2 is through respiratory air droplets. Although recent studies have revealed that the virus is detectable in the throat, blood, urine, anal swabs, tears and even faeces; however, modes of transmission other than respiratory droplets has not been studied much. Knowledge on the presence of the virus in the female genital tract may help determine the risk of sexual transmission as well as the risk of mother-to-child transmission. However, not much data are available yet regarding the presence of the virus in the female genital system. Hence, to explore the presence of the virus in the female genital system and possibility of sexual transmission, a study was conducted where in we tried to detect severe acute respiratory syndrome corona virus 2 in cervico-vaginal secretions. Methods: From July 2020 to September 2020, 35 COVID-19-positive female patients admitted to tertiary care teaching institute of Eastern India, which is now declared dedicated Corona Hospital and Centre of Excellence for COVID-19 care, who consented for the research were enrolled in this prospective observational study. Proper gynaecological history, clinical records along with laboratory findings of the patient was recorded. The possibility of the sexual transmission of the virus from female to her male partner was to be ascertained by testing the presence of severe acute respiratory syndrome corona virus 2 in the vaginal, cervical secretions by reverse transcriptase polymerase chain reaction. Results: All 35 COVID-19-positive female patients were tested for severe acute respiratory syndrome corona virus 2 in their vaginal and cervical secretions by reverse transcriptase polymerase chain reaction. All the samples were tested negative for the virus. Conclusion: Findings from this study reveals that severe acute respiratory syndrome corona virus 2 is not present in the cervical and vaginal secretions, and the possibility of transmission from female to her male partner by vaginal sexual intercourse is unlikely.